Propensão ao empreendedorismo: o caso dos discentes de uma ies no interior do Rio Grande do Norte - Santiago, Ana Gabriele Rodrigues de (Universidade Federal Rural do Semi-Árido, 2019)
Dornelas (2007) argues that the current moment can be called an era of entrepreneurship, because entrepreneurs are eliminating trade and cultural barriers and generating wealth for society. Higher Education Institutions (IES) play a fundamental role in the process of entrepreneurship training because it’s the students of undergraduate courses that will occupy positions in the labor market or will be owners of their own enterprises and promoters of their careers. Thus, this study focuses on the theme of entrepreneurship, taking as a research problem: do students of Applied Social Sciences’ area have a greater propensity for entrepreneurship? In this way, it’s interesting to investigate the propensity for entrepreneurship, comparing the students' perception of an University of the interior of Rio Grande do Norte considering the great areas of knowledge. The study is of a descriptive nature, having as a research tool a survey questionnaire, distributed through the e-mail list of the students, which received 506 answers that were the sample of this study. Data analysis was performed using categorical variables, frequencies and percentages. As for the metric variables in likert scale, we considered: the reliability analysis of the questions of the research instrument, the quality analysis of the answers obtained and the due statistical treatment of the data that were given by means of techniques with the aid of the statistical program: SPSS. As results of the study the data reveal that the respondents have entrepreneurial characteristics. The area of Applied Social Sciences presents a satisfactory propensity to the act of undertaking. In the four constructs the area reached an above average value ranging from 3.56 to 3.78 on a scale of 0 to 5, which represents a certain trend in the constructs reaching the sum of all variables of 99.40 points. The area that most stood out was the Human Sciences with a total of 116.46 points, the maximum score that could be reached was 135 points. On the other hand, the area with a less evident entrepreneurial profile was Biological Sciences with 93.5 points.
Monografia
Keywords: Propensão ao empreendedorismo; Empreendedorismo; Áreas do conhecimento; Propensity for entrepreneurship; Entrepreneurship; Areas of knowledge; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO